2016
DOI: 10.1016/j.theriogenology.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic reproductive tract measures and pelvis measures as predictors of pregnancy failure and anestrus in restricted bred beef heifers

Abstract: Previous reports have shown that reproductive tract score (RTS) can predict reproduction outcomes in seasonally bred beef heifers, although the accuracy can vary.Some ultrasonographic measures of the female reproductive tract and pelvis area have also been associated with reproductive outcome in young heifers. The objectives of this study were to determine which transrectal ultrasound or pelvis measures taken at a single examination are independent predictors of reproductive failure, and if the RTS system can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Also, in terms of ovarian development, the results of the present study are in agreement with the findings by Holm et al (2016) who did observe that the ovary length variables were independently associated with reproductive outcomes in this study (pregnancy failure). These authors also point out that one of the possible explanations for not finding a difference between ovary size and pregnancy failure may be due to a measurement error in ovary length at the time of data collection, thus making this analysis difficult.…”
Section: /7supporting
confidence: 93%
See 2 more Smart Citations
“…Also, in terms of ovarian development, the results of the present study are in agreement with the findings by Holm et al (2016) who did observe that the ovary length variables were independently associated with reproductive outcomes in this study (pregnancy failure). These authors also point out that one of the possible explanations for not finding a difference between ovary size and pregnancy failure may be due to a measurement error in ovary length at the time of data collection, thus making this analysis difficult.…”
Section: /7supporting
confidence: 93%
“…These physical conditions of the heifers could mean that they have already reached sexual maturity, and thus, the uterine development is complete, implying in an absence of interference of this variable on pregnancy rate. This fact was confirmed by Holm et al (2016) who, when evaluating genital development in heifers using ultrasonography, concluded that the development of the reproductive system is influenced both by age and live weight, and animals that have reached sexual maturity are not influenced anymore by the uterine diameter on conception or the pregnancy rate.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Logistic regression is an integral part of data analysis focused on exploring the strength and direction of associations between a dichotomous response variable and a set of potential predictors, and is widely used by researchers [1], [2], [3], [4], [5], [6]. In general, the goal of these research studies is to identify the set of true predictors that are incorporated in the final model which is used for classification, prediction or interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been proposed that puberty should be reached 45 days before the breeding season. [11][12][13] This developmental reproductive milestone would be influenced by the productive system, female physiology and genetics, 9,14,15 but the main factor that can be handled is nutrition under rearing.…”
Section: Introductionmentioning
confidence: 99%